Central Bank Digital Currency: the Next Money Revolution? Central Bank Digital Currencies in the Dimension of Geopolitics - Boros, Eszter; Horváth, Marcell (Public Finance Quarterly, 2022)
Throughout history, financial innovation was always interlinked with shifts in the word’s economic  centre of gravity and the emergence of new power hubs. Nowadays, the huge interest in central bank digital currencies proves that we must have arrived at a new turning point in the development of money. Most studies, however, focus on financial issues related to CBDCs, and only few embark on discussing historical analogies and geopolitical consequences in a comprehensive way. Our study aims to deliver such an analysis. According to the results, the revolutionary effects of CBDCs might arise from re-modelling cross-border payments, i.e., achieving direct (atomic) transactions through multilateral platforms. The remarkable results of China in developing the digital yuan, and most importantly, acquiring a key role in international projects, reinforce the geopolitical trends of the last decade. Global or regional standard-setting will be a critical question, and in this regard, there is still some room for manoeuvre on the side of the U.S. which started its own CBDC development (Project Hamilton) belatedly. In the long run, it might be realistic to expect a scenario in which the global financial system is divided in two parts, a Western and an Eastern one.